Recent developments in lipodystrophy. Issue 4 (August 2019) - Melvin, Audrey; Stears, Anna; Savage, David B.
Abstract : Purpose of review: Lipodystrophy syndromes have an estimated prevalence of 1.3–4.7 cases per million and as with other rare diseases conducting research can be challenging. The present review highlights recently published work that has provided insights into the field of non-HIV–associated lipodystrophy syndromes. Recent findings: Lipodystrophies are a heterogenous group of disorders, as such research is often focused on specific subtypes of the condition. The identification of children carrying LMNA mutations has provided insights into the natural history of FPLD2, specifically that the adipose tissue phenotype predates the onset of puberty. Recent reports of PLIN1 heterozygous null variant carriers and the apparent absence of a lipodystrophy phenotype challenges our understanding of the molecular biology of perilipin 1 and its role in the pathogenesis of FPLD4. With a focus on therapeutics, studies delineating the differential responsiveness of PPARγ mutants to endogenous and synthetic ligands has illustrated the potential for pharmacogenetics to inform therapeutic decisions in lipodystrophy related to PPARG mutations, whereas robust human studies have provided insight into the food independent metabolic effects of leptin in lipodystrophy. Finally, rare syndromes of lipodystrophy continue to serve as an exemplar for the contribution of genetically determined adipose tissue expandability to metabolic disease in the general population. Summary: Lipodystrophy research continues to illuminate our understanding of this rare disease and the possibility that lipodystrophy syndromes and the metabolic syndrome may have shared pathophysiology.